CLOUD TECHNOLOGY DISTANCE LEARNING IN HIGHER MATHEMATICS LEARNING PROCESS (Journal of Information Technologies in Education (ITE), 2014)
The article singles out four types of learning models: the model of distance education without the use of global networks, network model of e-learning, mobile learning model and the model of cloud technologies for distance learning can help you organize the teaching of Mathematics. Mentioned advantages and disadvantages of cloud technologies for distance learning.
Keywords: distance learning; distance education cloud technology; massive open distance learning course